Big data: The effect of analytics on marketing and business. Issue 2 (4th October 2022) - Manko, Barbara A.
Big data analytics takes raw, real-time data and uses it to predict trends. Successful use of this data can have a powerful impact on a business's effectiveness and ultimately their bottom line. As the amount of data increases, the need for analytics is growing. This teaching study discusses the role of social media in data analytics, how to approach the subject, and the desired outcomes. Students will explore the expansion of this field of study, familiarize themselves with the concept and where they may have encountered it in their lives so far, and discuss what analytics can contribute to running a successful business.